Violence risk assessment: science and practice - Douglas, Kevin S. (Legal and criminological psychology, 1999)
Within the conceptual framework of the scientist-practitioner model, this paper describes how the science of risk assessment has progressed to a point where it can be of definite assistance to clinicians. Similarly, clinicians can be of marked help to researchers as they play a role in concept definition and as they design and carry out studies to determine the accuracy of their predictions. Risk assessments ought to be carried out in accord with state-of-the-discipline knowledge. Until fairly recently, it may have been argued that the state of knowledge did not provide any sort of reliable or trustworthy direction on violence risk assessment. This position seems no longer tenable. Topic areas discussed include violence and risk assessment generally, the actuarial-clinical prediction debate, the validity of violence risk assessments, predictors of violence, violence risk assessment schemes (empirically validated structured clinical decision-making), communication of risk assessment findings, and implications for training.